Right to integrity for individuals deprived of liberty in double vulnerability through Habeas Corpus, ecuadorian jurisprudence 2023 - Laines Álvarez, Yolanda María; Ochoa Aguilar, Maritza Judith; Valarezo Enríquez, Gissela María; Aguilar Ochoa, Silvia Mayte (Revista Universidad de Guayaquil, 2025)
This study examines the jurisprudence of the Constitutional Court of Ecuador concerning the right to personal integrity and the habeas corpus remedy as a protective measure for individuals deprived of liberty, particularly those experiencing dual vulnerability. The central legal issue identified is the absence of clear criteria in the application of this judicial guarantee, as judges often fail to fully consider the circumstances necessary to prevent rights violations. The research methodology employed was the case study method, through which this issue was scrutinized by analyzing the jurisprudence of the Constitutional Court on violations of the right to personal integrity of individuals deprived of liberty who are in situations of dual vulnerability. A key aspect of this study is the judicial balancing of rights concerning individuals deprived of liberty in situations of dual vulnerability. The Constitutional Court of Ecuador has integrated various principles from the Inter-American Court of Human Rights to protect personal integrity through this judicial guarantee. Furthermore, the Court’s rulings carefully examine the circumstances to prevent any infringement of the rights of detainees, ensuring that these rights are effectively protected and enforced by constitutional judges. Consequently, this research concludes that judges must rigorously apply the principle of proportionality to enhance the effectiveness of this constitutional remedy, and the State must pursue a more effective penitentiary policy.